Pengaruh Struktur Umur Penduduk terhadap Pertumbuhan Ekonomi di Indonesia - Kurniawati, Endah; Sugiyanto, Catur (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
This study examines the effect of the population structure transition on economic growth using a panel data of 33 provinces in Indonesia from 2000 to 2015. The main working-age group has a positive effect on economic growth, while the middle age group has a negative effect. Furthermore, population growth has a negative effect on economic growth. The effect of population density on economic growth is very small. There is no difference on average economic growth inter-island in Indonesia except for Sulawesi Island which has a higher average economic growth compared to Java Island.